2016
DOI: 10.1016/j.apm.2015.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Semi-layerwise analysis of laminated plates with nonsingular delamination—The theorem of autocontinuity

Abstract: Available online xxxKeywords: Delamination Mixed mode II/III fracture Energy release rate Third-order plate theory Theoreom of autocontinuity a b s t r a c tThe proposed semi-layerwise approach captures the mechanical behavior of delaminated composite plates using four equivalent single layers independently of the lay-up. Two equivalent single layers are applied for both the top and bottom parts of a delaminated plate. The updated version of the system of exact kinematic conditions formulates the continuity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 121 publications
1
39
0
Order By: Relevance
“…As found, it is a reason of parametrically induced vibration of delaminated beams and plates [35][36][37]. Other studies confirmed the efficiency of the LW-based finite element models compared to those using the ESL approach [38,39] and showed that such models provide a stress recovery for localized effects [40].…”
Section: Introductionsupporting
confidence: 60%
“…As found, it is a reason of parametrically induced vibration of delaminated beams and plates [35][36][37]. Other studies confirmed the efficiency of the LW-based finite element models compared to those using the ESL approach [38,39] and showed that such models provide a stress recovery for localized effects [40].…”
Section: Introductionsupporting
confidence: 60%
“…However, the stress continuity results in a locking (over-constraining) problem in delaminated plates [105,106]. For the TSDT theory, one more set of conditions is reasonable to introduce.…”
Section: The Sekcmentioning
confidence: 99%
“…Figure 1(a) shows the deformation of the cross sections in the vicinity of the delamination tip in the X -Z plane for the core failure scenario (Scenario I). In the Y -Z plane, the deformation is similar [105,106]. The top and bottom facesheets are captured by an ESL and two ESLs are applied to the core.…”
Section: The Sekcmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally graded materials are novel composites whose composition changes continuously within the solid. In this way, concentrations of stresses between different constituent materials are avoided in contrast to layered composites [7], [8], [9]. By variation of their properties with specific gradients along spatial coordinates, functionally graded materials can be designed to satisfy different requirements in different parts of a member.…”
Section: Introductionmentioning
confidence: 99%